PENDEKATAN INQUIRI UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA SISWA - Rodiah Azma (Jurnal Evaluasi dan Pembelajaran, 2021)
The research objective was to increase the activity and achievement of learning mathematics from the Corruption Eradication Commission and FPB using the inquiry approach in grade V SD Negeri 4 Sawah Lama Bandar Lampung for the academic year 2019/2020. The research method was classroom action research (CAR) which was carried out in three cycles consisting of planning, implementation, observation and reflection in each cycle. The results showed an increase in learning activities in Cycle I 70%, Cycle II 80% and Cycle III 88% and learning achievement in cycle I averaged 62, cycle II 72, and cycle III 77. Based on the research results, the inquiry approach can increase activity and achievement. learn mathematics from the Corruption Eradication Commission and FPB in grade V SD Negeri 4 Sawah Lama Bandar Lampung for the 2019/2020 academic year. Keywords: Activities, Inquiries, Learning Achievement